2013
DOI: 10.1021/la303663x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy for Preparation of Graphene-Pd, Pt Composite, and Its Enhanced Electrocatalytic Activity for Alcohol Oxidation

Abstract: As advanced electrodes for direct alcohol fuel cells, graphene-Pd and graphene-Pt composites with a trace of SnO(2) have been successfully synthesized by a modified electroless plating technique. The surface of graphene oxide is first sensitized by Sn(2+) ions, and subsequently, Pd or Pt nanoparticles are deposited on the surface of graphene oxide. Finally, graphene oxide was reduced to graphene by further adding NaBH(4). Compared to other carbon-(e.g., Vulcan XC-72R) supported Pd and Pt, the resultant graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(113 citation statements)
references
References 39 publications
5
108
0
Order By: Relevance
“…The peaks located at 71.08 and 74.38 eV for Pt-Ag/GNs and at 71.38 and 74.79 eV for Pt/GNs can be assigned to the binding energies of Pt 4f 7/2 and Pt 4f 5/2 , respectively. Their values are in line with that of platinum in the zero-valent state, which further verifies the formation of Pt (0) nanoparticles in Pt/GNs and Pt-Ag/GNs composites [14]. However, the binding energy of Pt 4f for Pt-Ag/GNs is significantly lower than that for Pt/GNs.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The peaks located at 71.08 and 74.38 eV for Pt-Ag/GNs and at 71.38 and 74.79 eV for Pt/GNs can be assigned to the binding energies of Pt 4f 7/2 and Pt 4f 5/2 , respectively. Their values are in line with that of platinum in the zero-valent state, which further verifies the formation of Pt (0) nanoparticles in Pt/GNs and Pt-Ag/GNs composites [14]. However, the binding energy of Pt 4f for Pt-Ag/GNs is significantly lower than that for Pt/GNs.…”
Section: Introductionsupporting
confidence: 77%
“…Figure 4B shows Pt 4f spectra of Pt/GNs (curve a) and Pt-Ag/GNs (curve b [14]. However, the binding energy of Pt 4f for Pt-Ag/GNs is significantly lower than that for Pt/GNs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The slope of the plot ranged between 0.931 and 1.103 indicating that the reaction order is approximately unity, irrespective of potential. FeCo@Fe@Pd/C shows enhanced catalytic activities for MOR compared to many literature reports [44][45][46][47][48][49][50][51][52][53] as shown in ) showed a lower J f /J b ratio (2.60) indicative of a less active MOR in the anodic path compared to FeCo@Fe@Pd/C. Also, interestingly, despite that the loading of the Pd nanoflowers 52 is about 400 times higher than seen for FeCo@Fe@Pd/C, its J f /J b ratio (B5) is comparable with that of FeCo@Fe@Pd/C.…”
Section: à2mentioning
confidence: 70%
“…43 For preparing similar Pd-Pt bimetallic NPs, another anchoring with Sn 2+ was also reported. 44 Chen et al reported a synthetic method of Pt-Pd bimetallic nanocubes on RGO using N,N-dimethylformamide (DMF) as a bifunctional solvent for the reductions of both GO and metal ions and for confining the growth of Pt-Pd nanocubes on the surface. 10 By using the Pt-Pd bimetallic nanocube-RGO, nonenzymatic sensing of glucose at neutral pH was explored, and the performances were compared with the previous results obtained using seven different modified electrodes.…”
Section: ·1 Chemical Co-reduction Of Go and Metal Ionsmentioning
confidence: 99%